Reference analysis: Examination of the publications of the Journal of Health and Nursing Management (2014-2018) - Filiz Kantek; Hakan Kurnaz; Nezaket Yıldırım (Association of Nurse Managers, 2020)
INTRODUCTION: The aim of this study is to examine the references of the studies published in the Journal of Health and Nursing Management between 2014-2018 in terms of certain features. METHODS: The bibliometric analysis method was used in the study. In this retrospective descriptive study, the references of 101 studies published between 2014-2018 were examined. The data were analyzed by using SPSS and Excel programs. In the analysis of the data, distribution statistics, Kolmogorov-Smirnov test and t test were used. RESULTS: The total number of references in the published 101 studies was 3308, the average number of references is 32.79 + 13.88, the average number of references of research articles was 31.80 + 11.93, the reference age average age of references is 9.15 + 6.57 years and 67,51% of the reference were articles. The most frequently used journals were found to be the journals publishing in the field of nursing. DISCUSSION AND CONCLUSION: It can be said that the studies in the journal have strong and up-to-date references, and transmit scientific knowledge specific to the field based on the research results. Repeating this study and monitoring the results will contribute to improving the quality of the journal.